The Sexualization of Male Body in Perfume Advertisements in the Period of 2010-2013 - Soestasya Phinta (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
This research explains male body sexualization and discloses its motives in the 21st century’s American society through four perfume advertisements in the period of 2010 to 2013 which employ the unforeseen eroticized and sexualized images of men that raise questions among male body. This research is conducted using semiotics and socio-cultural approach. The findings show sexualization of male body is implemented through nudity, ambiguous sexuality and narrative tales & concepts in contemplation of extending market into metrosexual men, heterosexual women and homosexual men. They reveal the new portrayal of men’s masculinity –i.e metrosexuality.